Pelatihan Tempe Guna Meningkatkan Peluang Usaha Di Pasar Johar Kota Semarang - Haliz Nabilla Cahya Puteri; Oktarina Sinaga; Ghozy Fatkhur Rohman; Ausani Juliani Akhadun; Febiola Nur Azizah (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
In the current era of technological development, the application of conventional biotechnology can be seen in making tempeh, the manufacturing process of which uses fermented soybeans as raw materials with the help of microorganisms in the form of yeast. This tempe making training activity was held on April 20 2024 at Johar Market with a total of 29 participants. The method used in this training is to use the method of explaining the material and practicing directly. Based on the results of the training activities, there was an increase in participants' knowledge and abilities, this increase could be seen when the results of the questionnaire were distributed before and after the training was carried out. All participants know that tempeh is one of the foods most liked by the majority of Indonesian people. The speaker provided knowledge and experience regarding tempeh processing, when the participants already understood about tempeh processing, after that they carried out direct practice, up to the washing stage and entered the manufacturing stage. In this training, participants understand that tempeh has a fairly high source of vegetable protein and this training provides benefits and increases interest in opening up tempeh business opportunities.